Psychological Well-Being as a Mediator Between Psychological Contract Breach and Organisation Citizenship Behaviour (Medico Legal Update, 2019)
This paper is an attempt to study the negative impact of Psychological Contract Breach on Organisational Citizenship Behaviour in India and to explore the mediating effect of Psychological well-being of employees. It’s classic argument between the social exchange theory and the self-determination theory. A regression analysis is used to study the variables. The results confirm that positive organisational behaviours suppress the influence of psychological contract breach.